Employee Performance is Assessed in Terms of Work-Life Balance, Work-Family Conflict, Mental Health, and The Generation Gap - Dias Ratih Rahmandini; Istiatin Istiatin; Suhendro Suhendro (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to analyze the influence of work-life balance, work-family conflict, mental health, and the generation gap on employee performance at the Klaten Pratama Tax Office. This study uses a quantitative approach with a survey method. The study population was all Klaten Pratama Tax Office employees with a sample of 88 respondents. Data collection techniques were carried out through questionnaires, while data analysis used multiple linear regression with the help of the Statistical Product and Service Solutions (SPSS) program. Tests were conducted simultaneously and partially to determine the influence of each independent variable on employee performance. The results showed that work-life balance, work-family conflict, mental health, and the generation gap simultaneously influenced employee performance. Partially, work-life balance had a positive and significant effect on employee performance, mental health had a marginal effect, while work-family conflict and the generation gap had no significant effect. The coefficient of determination (R²) value of 0.274 indicates that the research variables were able to explain 27.4% of the variation in employee performance. This study concluded that work-life balance is the most dominant factor in influencing employee performance at the Klaten Pratama Tax Office.